Mifepristone alters amyloid precursor protein processing to preclude amyloid beta and also reduces tau pathology - Baglietto-Vargas, David; Medeiros, Rodrigo; Martinez-Coria, Hilda; LaFerla, Frank M.; Green, Kim N (Elsevier, 2013)
Background Increased circulating glucocorticoids are features of both aging and Alzheimer’s disease (AD), and increased glucocorticoids accelerate the accumulation of AD pathologies. Here, we analyzed the effects of the glucocorticoid receptor antagonist mifepristone (RU486) in the 3xTg-AD mouse model at an age where hippocampal damage leads to high circulating corticosterone levels. Methods The effects of mifepristone were investigated in 3xTg-AD mice using a combination of biochemical, histological, and behavior analyses. Results Mifepristone treatment rescues the pathologically induced cognitive impairments and markedly reduces amyloid beta (Aβ)-load and levels, as well as tau pathologies. Analysis of amyloid precursor protein (APP) processing revealed concomitant decreases in both APP C-terminal fragments C99 and C83 and the appearance of a larger 17-kDa C-terminal fragment. Hence, mifepristone induces a novel C-terminal cleavage of APP that prevents it being cleaved by α- or β-secretase, thereby precluding Aβ generation in the central nervous system; this cleavage and the production of the 17-kDa APP fragment was generated by a calcium-dependent cysteine protease. In addition, mifepristone treatment also reduced the phosphorylation and accumulation of tau, concomitant with reductions in p25. Notably, deficits in cyclic-AMP response element-binding protein signaling were restored with the treatment.
Keywords: Alzheimer, Enfermedad de; 3xTg-AD; Alzheimer's disease; Amyloid beta; Glucocorticoids; Mifepristone; Tau